Freshwater invasive alien crayfish species in South Africa: testing eDNA assessment and DNA barcoding - Mdidimba, Nonkazimulo Dorothea (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The expansion of the wild populations of the two invasive alien crayfish species, i.e., Cherax quadricarinatus and Procambarus clarkii in South Africa is of high concern. Given this, innovative and improved monitoring methods are required to be explored in order to effectively detect and manage their spread. Environmental DNA (eDNA) has shown promising and reliable results to detect and monitor alien crayfish in freshwater systems even at low densities. This research study aimed to field-test the application of eDNA for detecting and monitoring invasive alien freshwater crayfish species (IAFCs) in South African freshwater systems (Chapter 2). Further, this study also aimed to confirm the true taxonomic identity of the IAFCs in South African freshwater systems by using DNA barcoding to avoid potential misidentifications with morphological identification alone (Chapter 3). Also, ectocommensal temnocephalans and leeches attached to the crayfishes were also identified with DNA barcoding. The mitochondrial COI gene fragment of the crayfishes and the ectocommensal temnocephalans and leeches was amplified, sequenced, and used for species identification. For eDNA monitoring of C. cainii, C. quadricarinatus and P. clarkii, water samples were collected from Eastern Cape, Free State and KwaZulu Natal sites that are known to house these species. The current study did not detect the eDNA of the wild populations of both C. quadricarinatus and P. clarkii. This failure was encountered despite employing several methods, such as, end-point polymerase chain reaction (PCR), quantitative PCR (qPCR) and next-generation sequencing (NGS). The eDNA assessment to detect IAFCs in the wild populations is discussed in detail, and corrective measures suggested (Chapter 2). However, only C. cainii was able to be detected by eDNA. Cherax cainii is housed/farmed in an aquaculture facility (Vaughn Bursey's Stock Farm in Eastern Cape) with large number of individuals per pond. For this, NGS was able to detect C. cainii but the other two methods, end-point PCR and qPCR were not able to detect the species. Based on the results, refinement of eDNA monitoring methods for the South African freshwater systems is recommended. Evaluation of different DNA collection methods, preservation, DNA extraction kits and primer design to obtain effective eDNA detection is discussed as possible sources of error. Interestingly, the newly established population of P. clarkii in Mimosa Dam in Free State was infested with alien leeches, that were confirmed by DNA barcoding to be Helobdella europaea and Helobdella octatestica. Consequently, this study reports for the first time in South Africa the presence of this alien freshwater leeches. The presence of alien leeches and P. clarkii suggests a double invasion in Mimosa Dam, P. clarkii seems to continue expanding its range in the country. However, the long-established population of P. clarkii in Driehoek Farm in Mpumalanga, which has been in the country for over 30 years did not have any leech or temnocephalan infestation. This could suggest several interesting ecological phenomena, including environmental filtering over time of the co-invaders, differential source populations, and post-introduction adaptation.
Keywords: Introduced organisms -- South Africa; Crayfish; Leeches; Rhabdocoelida; Environmental DNA; DNA barcoding